AB0530 25-Hydroxyvitamin D3 Deficiency: Prevalance and Its Impact on Disease Activity in Small-Medium Vessel Vasculitis. (15th July 2016) - Korkmaz, F.N.; Ozen, G.; Unal, A.U.; Can, M.; Tuglular, S.; Direskeneli, H.
Abstract : Background: Growing evidence suggests that vitamin D has important immunomodulatory effects and plays key roles in endothelial dysfunction, atherosclerosis and pathogenesis/progression of some of the inflammatory rheumatic diseases such as rheumatoid arthritis and systemic lupus erythematosus. Although recent data indicated that vitamin D deficiency is quite prevalant and affects endothelial dysfunction in Behcet's Disease and Takayasu's arteritis, vitamin D levels in small/ medium vessel vasculitis and its effects on disease course have not been evaluated. Objectives: To determine the prevalance of 25-hidroxyvitamin D3 [25(OH)D3] deficiency and to investigate its effects on disease activity in patients with small and/or medium vessel vasculitis. Methods: In this cross-sectional study, 25(OH)D3 levels were measured in adult patients with systemic small-medium vessel vasculitis including ANCA-associated vasculitis (AAV), cryoglobulinemic vasculitis (CryV), IgA vasculitis (IgAV) and polyarteritis nodosa (PAN), and sex-matched healthy subjects (HS). All patients' baseline demographics, disease characteristics, acute phase reactants, medications and disease extents (DEI), disease activities (BVAS) and damage scores (VDI) were determined. 25(OH)D3 level <30ng/ml and <20ng/ml were regarded as insufficiency and deficiency, respectively. Results: Forty five patients (29% new diagnosis) with systemic vasculitis and 63 HS were included ( Table 1 ). The mean 25(OH)D3 level was 21.8±14.3 ng/mL in patients with vasculitis and 56.7±23.9 ng/mL in HS (p<0.001). Vitamin D insufficiency and deficiency were significantly higher in patients with vasculitis compared to HS ( Table 1 ). Thirty eight patients (84.4%) were active (BVAS≥1) at the time of recruitment. 25(OH)D3 levels were not different in active (21.6±14.8) and inactive (23.1±12.1) patients (p=0.79). Of the 24 vitamin D deficient patients 23 (95.8%) had renal involvement. Vitamin D deficient patients had slightly higher BVAS (6.5±6.7 vs 3.7±3.7), VDI (3.8±1.4 vs 3.2±1.3) and DEI (3.0±2.8 vs 1.8±2.4) scores at recruitment but the differences were not statistically significant (p>0.05). Likewise there was no difference in acute phase reactants according to vitamin D status. Conclusions: Vitamin D insufficiency and deficiency are quite common in patients with small/medium vessel systemic vasculitis. In this preliminary study we could not demonstrate any association with vitamin D deficiency and disease activity in patients with vasculitis. However, prospective followup of a larger sample would better clarify the role of vitamin D on disease activity. Considering also the use of high dose glucocorticoid treatment, these patients should be adequately evalauted and treated for vitamin D deficiency. Disclosure of Interest: None declared